Learned helplessness and the facilitation of biofeedback performance - Traub, G S; May, Jr, J G (Biofeedback and self-regulation, 1983)
The present article reports the results of two studies, which, taken together, support the hypothesis that learned helplessness resulting in effort cessation, while detrimental to performance on cognitive tasks, is actually facilitative to performance in a biofeedback relaxation task. Data are presented indicating that false failure feedback leads to the typically reported decrement in performance on a cognitive arithmetic task, while such feedback leads to enhanced performance in biofeedback relaxation. Self-report data suggest that this occurs because when subjects encounter failure, they revise their expectancies of future success downward and consequently plan to exert less effort. Reduction of effort is proposed as the common mechanism underlying the contrast in results between the arithmetic and biofeedback tasks. Results are discussed in terms of their implications for the way in which theories of self-efficacy and learned helplessness are commonly interpreted.